Dietary Protein and Fat as Predictors of Hypertension Incidence in the Coastal Community of Basule Village, Lasolo District - Syaputri Adli, Rizky; Rahmawati, Rahmawati; Herpianti Lolok, Nike (Waluya The International Science of Health Journal, 2025)
Introduction: A preliminary survey of 10 coastal residents of Basule Village revealed that 80% had hypertension and 20% did not have hypertension. A 24-hour recall showed that 70% of macronutrient intakes, consisting of protein, fat, and carbohydrates, were in the excess category, while 80% of micronutrient intakes were in the excess category. This study aimed to analyze the relationship between protein and fat intake and the incidence of hypertension in the coastal community of Basule Village, Lasolo District. Method:The type of research used was quantitative through observation, the research design used a Cross Sectional Study. The population was 247 people and 153 samples used the Slovin formula, sampling used Purposive Sampling. Result:The Chi-Square test obtained a p value of 0.000 < α (0.05), φ (0.496) and X2 Calculation (37.594) > X2 Table (5.991) there is a moderate relationship between the protein aspect and the Chi-Square test obtained a p value of 0.023 < α (0.05), φ (0.221) and X2 Calculation (7.506) > X2 Table (5.991) there is a weak relationship between fat intake and the incidence of hypertension in the coastal community of Basule Village, Lasolo District. Conclusion:There is a moderate relationship between protein intake and a weak relationship between fat intake and the incidence of hypertension in the coastal community of Basule Village, Lasolo District.